Orientasi Keilmuan Santri Pondok Pesantren di Tiga Kabupaten di Jawa Tengah - Abdul Rohman (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
This survey, carried out in Cilacap, Banyumas, and Banjarnegara, all in Central Java, attempts to identify students’ motivation in entering traditional Muslim boarding schools and their knowledge orientation. Primary data were obtained from interviews with the students and the teachers of the Muslim boarding schools, religious leaders, and other resource persons related to the schools. Secondary data were in the form of documents, including institutional documents, curricula, and relevant research findings. The statistical data show that 59% of the students were studying at formal educational institutions, planned to further their study, and tended to choose universities as their first priority; 38% placed universities for Islamic studies as their second priority; and 3% gave no response. The students tended to choose universities because they thought that university graduates would get jobs more easily, because they had planned it since childhood, or because they wanted to better prepare for this changing world.